2006
DOI: 10.1187/cbe.06-02-0144
|View full text |Cite
|
Sign up to set email alerts
|

An Intensive Primary-Literature–based Teaching Program Directly Benefits Undergraduate Science Majors and Facilitates Their Transition to Doctoral Programs

Abstract: UCLA's Howard Hughes Undergraduate Research Program (HHURP), a collaboration between the College of Letters and Science and the School of Medicine, trains a group of highly motivated undergraduates through mentored research enhanced by a rigorous seminar course. The course is centered on the presentation and critical analysis of scientific journal articles as well as the students' own research. This article describes the components and objectives of the HHURP and discusses the results of three program assessme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
72
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(76 citation statements)
references
References 4 publications
2
72
0
2
Order By: Relevance
“…The combination of interactive seminars from experts and journal clubs had previously demonstrated benefits for high achieving, research-streamed students (Kozeracki, Carey, Colicelli, & Levis-Fitzgerald, 2006), but here the whole cohort is involved. There were three primary aims of this modification:…”
Section: Introductionmentioning
confidence: 99%
“…The combination of interactive seminars from experts and journal clubs had previously demonstrated benefits for high achieving, research-streamed students (Kozeracki, Carey, Colicelli, & Levis-Fitzgerald, 2006), but here the whole cohort is involved. There were three primary aims of this modification:…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a large body of research supports the integration of information literacy and librarians into science courses to improve the science literacy of students and help them find and use literature in their fields (Kingsley et al, 2011;Klucevsek & Brungard, 2016;Kozeracki, Carey, Colicelli, & Levis-Fitzgerald, 2006;Krontiris-Litowitz, 2013;Reisner, 2016;Thompson & Blankinship, 2015).…”
Section: Klucevsekmentioning
confidence: 99%
“…There is a lot of research suggesting beneficial effects of explicit instruction in critical thinking on learning (e.g. Fortner 1999, Herman 1999, Kozeracki et al 2006, Hoskins et al 2007and Gehring and Eastman 2008. Kozeracki et al (2006) described a specially designed course to train undergraduates in the critical analysis of scientific journals.…”
Section: Introductionmentioning
confidence: 99%
“…Fortner 1999, Herman 1999, Kozeracki et al 2006, Hoskins et al 2007and Gehring and Eastman 2008. Kozeracki et al (2006) described a specially designed course to train undergraduates in the critical analysis of scientific journals. The results showed that students trained under the programme demonstrated increased ability to read and present scientific research as well as increased in confidence.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation